GOFOOD APPLICATION USERS CONSUMER BENEFITS IN ELECTRONIC TRADE TRANSACTIONS - Nizla Rohaya; Fokky Fuad Wasitaatmadja (Jurnal Hukum Replik, 2021)
This study is a form of the author's academic anxiety in observing the consumer behavior of users of one of the Gojek applications, namely GoFood, which recently, consciously, and intentionally has committed a default act of canceling the food delivery service after the GoFood driver bailed out with his own money to buy an order. consumer. This act of course caused a huge loss for GoFood drivers who incidentally are small people who are trying to make a living to meet the needs of their families. The research method used in this study is a normative research method with a statute approach as well as a case approach. The authors took both approaches because there are no rules in positive law in Indonesia that regulate the problems to be studied. From the results of the study, it was found that for acts of default by consumers who cancel orders unilaterally and irresponsibly, only civil sanctions can be imposed so that it is not enough to cause a deterrent effect for consumers who have bad intentions. So, it is time for regulators to formulate forms of criminal sanctions against consumers who knowingly and intentionally cancel orders to the detriment of GoFood drivers, as has been formulated by the Philippine government.Keywords: Gojek, GoFood, Online Drivers, and Consumers.